Pengaruh Brand Equity Terhadap Loyalitas Konsumen Produk Air Minum Dalam Kemasan (AMDK) Merk Aqua Di Bandar Lampung - Agus Purnomo (SOSIALITA, 2011)
The purpose of this research is to know the consumer’s loyalty of AMDK product branded AQUA in Bandar Lampung. The research problems are: 1) Is there any individual influence of product, image, and visual to consumer’s loyalty AQUA product in Bandar Lampung? 2) Is there simultaneous influence of product, image, and visual to consumer’s loyalty AQUA product in Bandar Lampung. The research used double linear regression. In this model, product, image, and visual as independent variables and consumer’s loyalty as dependent variable. To analyze independent variables influence to dependent variable individually, is used t test. On the other hand, to analyze the influence of independent variables to dependent variable simultaneously, is used F test. 100 samples were collected by judgement sampling and data were collected by questionnaire. The result of this research showed that product, image and visual individually influence consumer’s loyalty of AQUA product in Bandar Lampung positively and significantly, it’s proved by t significant value 0,000, and t coefficient values of the third independent variables are 6,615, 7,468, and 6,276. Product, image, and visual also simultaneously influence consumer’s loyalty of AQUA product in Bandar Lampung positively and significantly with F coefficients value 90,424, and significant value 0,000. 0,739 R square mean that 73,9% of AMDK AQUA consumer’s loyalty is defined by product, image and visual, while the rest are defined by other variable.